Proteome and Proteomics: from Single Protein to Whole Body - Tarassishin Leonid (Journal of Proteomics and Genomics Research, 2014)
A primer explains how proteomics scales from single‑protein analysis to whole‑organism studies, touching on technologies, bioinformatics, and applications.
Keywords: Proteome